The Contribution of Yam Farming Activities To Livelihood of Farmers In Ekiti State, Nigeria - Sola Emmanuel Komolafe; Gbolagade Benjamin Adesiji; Sheu-Usman Oladipo Akanbi (Jambura Agribusiness Journal, 2022)
Innovative opportunity in agricultural entrepreneurship skills is an important factor for sustainable livelihood of farmers. Yam cultivation, processing, transporting and marketing are major strategies for livelihood among farmers in Nigeria. This study therefore assessed the impact of yam entrepreneurial activities in Ekiti state, Nigeria. The study was conducted in Ekiti State, Nigeria. A total of 580 yam farmers were sampled. An interview schedule was designed to collect primary data. Frequency count, percentage, mean score and ordered probit regression were used to analyse data collected. The study showed that personal savings was the main sources of capital (69.7%), only few were member of farmers’ group (66.2%). Also, average farm workers was 3 persons and average hours devoted for yam farming activities per day was 5hours. Aside yam cultivation activity, farmers were mostly involved in yam marketing (mean=0.99), transporting (mean=0.94) and processing (mean=0.60). Findings show that farmers’ participation in yam entrepreneurial activities had contributed significantly (p≤0.5) to financial, physical, social, human and natural assets of farmers in Ekiti State.